The effect of including a series of isometric conditioning contractions to the rowing warm-up on 1,000-m rowing ergometer time trial performance - Feros, S. A.; Young, W. B.; Rice, A. J.; Talpey, S. W. (The Journal of Strength and Conditioning Research, 2012)
Rowing requires strength, power, and strength-endurance for optimal performance. A rowing-based warm-up could be enhanced by exploiting the postactivation potentiation (PAP) phenomenon, acutely enhancing power output at the beginning of a race where it is needed most. Minimal research has investigated the effects of PAP on events of longer duration (i.e. 1,000-m rowing). The purpose of this research was to investigate the effects of PAP on 1,000-m rowing ergometer performance through the use of 2 different warm-up procedures: (a) a rowing warm-up combined with a series of isometric conditioning contractions, known as the potentiated warm-up (PW), and (b) a rowing warm-up only (NW). The isometric conditioning contractions in the PW were performed by "pulling" an immovable handle on the rowing ergometer, consisting of 5 sets of 5 seconds (2 seconds at submaximal intensity, and 3 seconds at maximal intensity), with a 15-second recovery between sets. The 1,000-m rowing ergometer time trial was performed after each warm-up condition, whereby mean power output, mean stroke rate, and split time were assessed every 100 m. Ten Australian national level rowers served as the subjects and performed both conditions in a counterbalanced order on separate days. The PW reduced 1,000-m time by 0.8% (p > 0.05). The PW improved mean power output by 6.6% (p < 0.01) and mean stroke rate by 5.2% (p < 0.01) over the first 500 m; resulting in a reduction of 500-m time by 1.9% (p < 0.01), compared with the NW. It appears that the inclusion of isometric conditioning contractions to the rowing warm-up enhance short-term rowing ergometer performance (especially at the start of a race) to a greater extent than a rowing warm-up alone